FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH MENABUNG DI BANK MUAMALAT INDONESIA - Deftyan Hadi Pratita; Sri Herianingrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This study used a quantitative approach using factor exploratory analysis. In this study, the characteristic of the population were customers‟ of Bank Muamalat Indonesia in Surabaya. Pre eliminary test was conducted by using focus group discussion to 10 customers, while for the main test used simple random sampling with probability sampling as the sampling method towards 100 customers. According to the result, there are eight factors that influence customers‟ saving decision in Bank Muamalat Indonesia. Those factors are the reduction result from the factor analysis process. Those eight factors are services provider, normative perception, clear information, process, the product‟s syariah value, referrals, environment suitability and office layout design.  REFERENCESAlamsyah, Halim. 2012, Perkembangan dan Prospek Perbankan Syariah, Indonesia. IAEI.Anshori Muslich dan Sri Iswati. 2009. Buku Ajar Metodologi Penelitian Kuantitatif. Surabaya: Pusat Penerbitan dan Percetakan UNAIR (AUP).Antonio, Muhammad Syafii. 2001, Bank  Syariah Dari Teori ke Praktek. Gema Insani Press bekerja sama dengan Yayasan Tazkia Cendekia.Assael, Henry. 1998. Consumer Behavior and Marketing Action. Sixth Edition. Massachussets: Kent Publishing Company.Departemen Agama RI. 2011. Al-Qur'an Gitosudarmo, Indriyo. 2004. Manajemen Pemasaran. Edisi Pertama Cetakan Keenam.BPFE-Yogyakarta.Kotler, Philip dan AB. Susanto.2001. Manajemen Pemasaran Indonesia.Buku 2.Salemba empat. Jakarta.--------, John Bowen and James Makens.2002. Pemasaran Perhotelan dan Kepariwisataan.Edisi 2. Jakarta: PT Prenhallindo.--------. 2004. Prinsip-prinsip Pemasaran Jilid II. Jakarta: Erlangga.--------, dan Kevin Lane Keller. 2009. Manajemen Pemasaran. Edisi 14.Jakarta: Erlangga.Malhotra, Naresh K. 2010. Riset pemasaran: Pendekatan Terapan. Jilid 1.Jakarta: PT. Indeks.Ratnasari, Ririn Tri. 2012. Konsep Dasar Syariah Marketing.Slide kuliah Manajemen Pemasaran Syariah.Pertemuan 1.Departemen Ekonomi Islam Fakultas Ekonomi dan Bisnis Universitas Airlangga.--------. 2012. Manajemen Pemasaran Islam. Modul 1. Surabaya: Departemen Ekonomi Syariah Fakultas Ekonomi dan Bisnis Universitas Airlangga.-------- dan Nisful Laila. 2012. Measuring Customer Service Quality Based on Fatanah Implementation. Proceedings of 2nd Global Islamic Marketing Conference (GIMC).Abu Dhabi.Ratnawati, Anny. 2011."Potensi dan Strategi Pengembangan Bank Syariah di Indonesia",vol.9, no. 2.Sugiyono.2010. Metode Penelitian Kuantitatif Kualitatif. Bandung: Alfabeta.Sutisna.2001. Perilaku Konsumen dan Komunikasi Pemasaran. Bandung: PT. Remaja Rosdakarya.